2005
DOI: 10.5558/tfc81031-1
|View full text |Cite
|
Sign up to set email alerts
|

Upland black spruce stand development 17 years after cleaning and precommercial thinning

Abstract: Density management is often used by silviculturists to guide stand composition and development. We examined the effects of cleaning (hardwood removal) and four levels of precommercial thinning (0, 20, 35 and 50% basal area removal) on stand development in a dense, 24-year-old upland black spruce (Picea mariana [Mill.] BSP) plantation near Beardmore, Ontario. Immediately before treatment, stand densities and basal areas for all species and for black spruce averaged 7375 and 6415 stems ha -1 , and 27.9 and 20.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
2
6
0
Order By: Relevance
“…The response of diameter growth is greatest in stands with an intensive and early PCT, as reported earlier by Varmola (1996), Ruha and Varmola (1997), Varmola et al (1998), Varmola and Salminen 2004. Similar results on the growth response to precommercial thinning have also been reported in studies in Canada by Tong and Zhang (2005) for jack pine, by Johnstone (2005) for lodgepole pine, by Fleming et al (2005) for black spruce, and by Pothier (2002) for balsam fir.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The response of diameter growth is greatest in stands with an intensive and early PCT, as reported earlier by Varmola (1996), Ruha and Varmola (1997), Varmola et al (1998), Varmola and Salminen 2004. Similar results on the growth response to precommercial thinning have also been reported in studies in Canada by Tong and Zhang (2005) for jack pine, by Johnstone (2005) for lodgepole pine, by Fleming et al (2005) for black spruce, and by Pothier (2002) for balsam fir.…”
Section: Discussionsupporting
confidence: 73%
“…In recent studies in Canada, precommercial thinning was reported to have positively affected merchantable stem volume production (Tong andZhang 2005, andJohnstone 2005). In contrast, Fleming et al (2005) found that cleaning improved black spruce growth, but precommercial thinning resulted in only a slight increase in mean tree size but a larger reduction in merchantable stand volume. Pothier (2002) also found that precommercial thinning did not increase the merchantable wood volume at maturity but, on the other hand, he found that thinning improved the yield composed of large diameter trees (≥15.1 cm), while obviously the effect of the treatments on wood volume depends on the minimum usable diameter in question.…”
Section: Discussionmentioning
confidence: 67%
“…However, delaying a young stand management operation increases an impending consumption of working time (Kaila et al 2006) and decreases diameter growth of crop trees (Pothier 2002, Fleming et al 2005, Pitt and Lanteigne 2008 and is in generally reasonable only if it enables to avoid some of later management operations. Anyhow, similar procedure could also be performed in spot-mounded site by delaying early cleaning.…”
Section: Discussionmentioning
confidence: 99%
“…Disadvantage caused by competition depends on the distance and height difference between the crop tree and the disturbing tree (Andersson 1993, Laaksonen 2008). Therefore, a properly timed pre-commercial thinning accelerates or at least sustains growth of crop trees (Folkesson and Bärring 1982, Pothier 2002, Fleming et al 2005, Huuskonen and Hynynen 2006, Pitt and Lanteigne 2008.…”
Section: Introductionmentioning
confidence: 99%
“…B.S.P.) were weak or even negligible in some experiments (e.g., McClain et al 1994, Fleming et al 2005, but good growth responses have been obtained on productive sites (Karsh et al 1994, Newton andWeetman 1994). Experiments conducted in the eastern United States and Canada also have reported significant DBH growth increases to PCT for northern hardwoods including paper birch (Betula papyrifera Marsh.)…”
Section: Introductionmentioning
confidence: 94%